Proyecto de vinculación familia-escuela - Saca Plasencia, Nancy Maricela (2016)
The integration of parents and family mothers in the educational institution is the base that will mark the future of the student, it´s a responsibility of the family to control the school tasks of his children and teenagers who come to the institution, reason for which it is necessary to strengthen the relations of the educational community, socialization the regulation on the rights and obligations of the representatives with the purpose of acquiring the commitment in the educational community and in the formation academic of the children and girls by means of the participation and collaboration in the school activities helping the teacher in his arduous labor of forming persons critical, reflexive and capable of giving solutions to social problems. One of the difficulties has been the ignorance of legal documents in the educational area on the part of the legal representatives giving, giving like result an unfavorable communication and participation between the family and the school, causing the low academic performance in the students of the seventh year of Basic General Education at Municipal school " Ing. Guillermo Sotomayor Navas", the methods that were in use were the descriptive investigation of type, camp - bibliographical applying the methods deductively - inductively and instruments as surveys you interview. We identify the existing problem in the institution especially un the children and the girls of the seventh year, so the implementation is necessary an internal regulation committing the father and the family mother to the participation and to give to the continuation in the tasks of the school, achieving a significant contribution in the personal and professional development of the student. It will take four hundred eighty-seven students and fifteen teachers as beneficiaries those wh0 will approve y the application of the regulation inside the educational ambit.